Process method for inhibiting generation of micro-nano structure machining burrs
By spin-coating UV glue to form a protective layer with adjustable thickness and hardness, it suppresses the generation of burrs during micro-nano structure processing, and uses a two-step efficient cleaning process of solvent and plasma to remove the protective layer, solving the burr suppression in the prior art and the shortcomings of removal methods have achieved efficient processing of micro-nano structures and improved surface quality.
Patent Information
- Application Number
- CN202411768801.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-04
AI Technical Summary
During the micro-nano structure processing, the prior art is difficult to effectively suppress the generation of burrs, and the existing removal methods cause great damage to the micro-nano structure and have poor applicability.
The thickness and hardness are formed by spin-coating UV glue to form a protective layer with adjustable thickness and hardness, and burrs are prevented from forming lateral plastic flow of the boundary material. Then, the protective layer is removed by using a two-step efficient cleaning process of solvent and plasma to ensure surface quality.
It realizes effective suppression of burrs during micro-nano structure processing, ensures the finish and performance of the workpiece surface, and the cleaning process will not damage the processed structure and improves the surface quality.
Smart Images

Figure CN119456361A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of workpiece micro-machining, and in particular to a process method for suppressing the generation of burrs during micro-nano structure machining. Background Art
[0002] Cutting is the best manufacturing technology for micro-nano structures with complex morphology. In recent years, in order to adapt to the development of semiconductors and other industries, cutting technology is developing towards the micro-nano scale. Burrs are material residues on the surface of workpieces, which are caused by the plastic deformation and flow of materials squeezed by the tool during the machining process. Burrs will reduce the surface quality of the workpiece and weaken the performance of the surface of the micro-nano structure. Therefore, it is extremely important to inhibit the generation of burrs or eliminate the burrs of micro-nano structures. In terms of eliminating burrs, there are currently methods such as manual removal, mechanical removal, chemical removal, heat treatment, pneumatic tool removal and laser removal, but the above methods will destroy the micro-nano structure, so they are not suitable for eliminating burrs of micro-nano structures. In the process of micro-nano structure processing, burrs can also be reduced as much as possible by optimizing process parameters and improving tool quality, but these methods have limited effects and cannot fundamentally prevent the generation of burrs.
[0003] During the cutting process, for plastic materials such as aluminum, copper, and polypropylene plastic, the workpiece material will be plastically deformed by the cutting force of the tool, and the cut part will break and become chips to be removed, while some of the boundary materials will flow to the side workpiece surface due to extrusion to form burrs. To solve this problem, a protective layer can be prepared on the workpiece surface. The protective layer covers the workpiece surface under the processing surface, so that the lateral plastic flow of the original boundary material is blocked during the cutting process, and only the protective layer material will form burrs on the surface, thereby achieving the purpose of suppressing the formation of burrs on the workpiece surface. After the processing is completed, the protective layer can be removed through subsequent treatment to obtain a burr-free and smooth surface structure.
[0004] However, the existing coating protective layer cutting technology uses materials such as polymethyl methacrylate (PMMA) and paraffin as the protective layer. First, the thickness of the protective layer should be related to the plastic flow characteristics of the material, the hardness of the protective layer and the size of the theoretical burr. The coating thickness of PMMA and paraffin protective layers is difficult to control accurately. For micro-nano structure processing, the cutting amount is very small, and the thickness control accuracy of the protective layer will directly affect the depth and aspect ratio of the processed micro-nano structure. Secondly, the hardness of the protective layer is optimal when it is 70% to 90% of the hardness of the workpiece. The hardness of traditional protective layer materials such as PMMA and paraffin is constant. For example, the hardness of PMMA is 60-75 Shore D, and the plastic materials it can adapt to are very limited. The hardness and adhesion of paraffin are very poor, and it cannot prevent the plastic flow and deformation of plastic materials, and the inhibitory effect on burrs is very limited. Finally, it is necessary to remove the protective layer through a cleaning process to obtain a burr-free and smooth surface structure. For the polymethyl methacrylate protective layer, the organic solution acetone is usually used to clean the protective layer after cutting. However, acetone cannot completely remove the protective layer, so the residue will contaminate the surface of the workpiece, thereby affecting the surface quality.
[0005] Therefore, in order to achieve burr suppression in micro-nanostructure processing of various materials, it is necessary to prepare a protective layer with adjustable thickness and hardness, and at the same time, the protective layer needs to be efficiently cleaned and processed. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a process method for suppressing the generation of burrs in micro-nano structure processing, which solves the problems of burr generation in the prior processing technology and the cumbersome and poor adaptability of the burr post-processing process.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: A process method for suppressing the generation of burrs in micro-nano structure processing, comprising the following steps:
[0008] S1. Surface preparation
[0009] First, the surface of the plastic material workpiece is cleaned and dried;
[0010] S2. Spin coating UV adhesive protective layer
[0011] The UV glue is spin-coated onto the surface of the workpiece by a glue spreader to form a UV light-curing protective layer, and the thickness of the UV light-curing protective layer is controlled to be 2-30 μm by controlling the spin-coating speed and time;
[0012] S3. UV curing and thermal baking
[0013] The spin-coated workpiece is placed in a UV curing machine to cure the UV light-cured protective layer by ultraviolet light for 10-40 seconds, and then heat-dried at a temperature of 150-200°C for 5-10 minutes to regulate the hardness of the photoresist protective layer;
[0014] S4. Machining
[0015] The processed workpieces are subjected to mechanical processing, and the processing methods include but are not limited to single-point turning, milling, high-speed fly cutting and ultrasonic vibration-assisted cutting. The processed structure must be a non-adjacent structure including a boss;
[0016] S5. Solution immersion treatment
[0017] Soak the processed workpiece in the photoresist cleaning agent for 10 minutes;
[0018] S6. Plasma treatment
[0019] Use oxygen plasma equipment to treat the workpiece after solution immersion;
[0020] S7. Final surface treatment
[0021] The workpiece after the above treatment is cleaned to completely remove the UV light-cured protective layer and then dried to obtain a finished smooth workpiece without burrs.
[0022] Preferably, in the step S2, when the workpiece to be processed is a material with poor adhesion to the UV glue, the surface of the workpiece is first subjected to an adhesion enhancement treatment before spin coating, and the adhesion enhancement treatment includes but is not limited to electroplating, thermal spraying and vapor deposition; the UV light-curing protective layer includes but is not limited to UV photoresist used in photolithography processes and UV glue used for bonding and packaging.
[0023] Preferably, the processed structures in step S4 include but are not limited to holes, trapezoidal grooves and serpentine grooves.
[0024] Preferably, in step S5, the photoresist cleaning agent includes but is not limited to an organic solvent, an acidic or alkaline photoresist cleaning agent.
[0025] Preferably, in the step S6, the plasma equipment includes but is not limited to a plasma jet and a plasma chamber, and the processing atmosphere may be atmospheric or vacuum.
[0026] Preferably, the S6 step is specifically as follows:
[0027] The workpiece after immersion treatment is placed in a vacuum plasma chamber, O2 plasma is excited, and high-energy particles react with the UV light-cured protective layer through chemical reactions to generate gaseous reactants to remove the protective layer. The RF power frequency is 13.56MHz, the input power is 600W, O2 and CF4 are used as reaction gases, the flow rate is 200sccm O2+100sccm CF4, and the processing time is 15min.
[0028] The present invention provides a process for suppressing the generation of burrs in micro-nano structure processing. It has the following beneficial effects:
[0029] 1. The present invention controls the thickness of the protective layer by controlling the spin coating speed and time of the UV glue, and controls the hardness of the protective layer by controlling the light curing and heat baking time, thereby preparing a protective layer with controllable hardness to prevent burrs from being formed by lateral plastic flow of boundary materials during micro-nano structure processing, and is applicable to a variety of processed materials.
[0030] 2. The present invention uses a two-step efficient cleaning process of solvent combined with plasma. First, most of the UV light-cured protective layer is removed by solution immersion, which greatly saves the cost and time of subsequent plasma treatment. Then, oxygen plasma is used to further enhance the cleaning ability, and the cleaning effect is more significant. Compared with the use of acidic and alkaline solutions for cleaning, which may cause corrosion to the surface, plasma cleaning will not damage the processed structure, the surface quality is higher, and efficient and clean cleaning of the residual protective layer is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Embodiment 1:
[0034] like Figure 1 As shown, an embodiment of the present invention provides a process method for suppressing the generation of burrs in micro-nano structure processing, comprising the following steps:
[0035] S1. Surface preparation
[0036] First, the surface of the plastic material workpiece is cleaned and dried.
[0037] S2. Spin coating UV adhesive protective layer
[0038] UV glue is spin-coated onto the surface of the workpiece by a glue spreader to form a UV light-curing protective layer. The thickness of the UV light-curing protective layer is kept at 30 μm by controlling the spin-coating speed and time. In order to ensure the burr suppression function of the UV light-curing protective layer, the thickness of the protective layer needs to be controlled to be 3 times the burr size. The burr size in the cutting process is usually 10 μm, so the thickness of the protective layer needs to be adjusted according to the processing material and the thickness of the burrs generated in the specific process. When the workpiece to be processed is a material with poor adhesion to the UV glue, the surface of the workpiece is first subjected to an adhesion enhancement treatment before spin coating. The adhesion enhancement treatment includes but is not limited to electroplating, thermal spraying and vapor deposition. The UV light-curing protective layer includes but is not limited to UV photoresist used in photolithography and UV glue used for bonding and packaging.
[0039] S3. UV curing and thermal baking
[0040] Place the spin-coated workpiece in a UV curing machine, and cure the UV light-cured protective layer by ultraviolet light for 40 seconds, and then heat-bake it at 200°C for 10 minutes; to ensure the burr suppression function of the UV light-cured protective layer, the hardness of the protective layer needs to be controlled. If the UV light curing time is insufficient, the hardness of the protective layer will be too low, and the burr suppression transfer function cannot be achieved. In order to maximize the burr suppression effect, the hardness of the protective layer needs to be controlled to 70% to 90% of the hardness of the workpiece. Depending on the material of the workpiece and the size of the micro-nano structure, the light curing and heat-bake time are controlled to adjust the hardness of the protective layer, and the hardness is finally controlled to 45 to 90 shoreD.
[0041] S4. Machining
[0042] The processed workpiece is subjected to mechanical processing. The processing methods include but are not limited to single-point turning, milling, high-speed fly cutting and ultrasonic vibration-assisted cutting. In order to ensure the applicability of the process, the cutting structure must be a non-adjacent structure containing a plane to ensure that the burr can be transferred to the protective layer. The processing structure includes but is not limited to holes, trapezoidal grooves and serpentine grooves.
[0043] S5. Solution immersion treatment
[0044] Soak the processed workpiece in a photoresist cleaning agent for 10 minutes. For UV light-cured protective layer materials, the main component is an organic polymer. The photoresist cleaning agent used includes but is not limited to inorganic solvents, acidic and alkaline reagents. Depending on the workpiece material, in order to avoid damage to the processed structure caused by acid and alkali corrosion, the workpiece is often soaked in solvents such as acetone and alcohol to remove the protective layer material. At the same time, in order to improve processing efficiency, an ultrasonic cleaning device can be used during the solution immersion process.
[0045] S6. Plasma treatment
[0046] The workpiece after immersion treatment is placed in a vacuum plasma chamber, O2 is used as the reaction gas, CF4 is used as the auxiliary gas, and O2 plasma is excited by a radio frequency power supply in the vacuum chamber through a capacitive coupling method. The main component of the UV light-cured protective layer is carbon-containing organic matter. The high-energy particles in the plasma react with the protective layer to generate CO2 and other gases and are discharged, thereby achieving a cleaning effect and removing the UV light-cured protective layer. This process does not require the introduction of Ar as a medium gas; when O2 and CF4 are introduced at a ratio of 2:1, the plasma cleaning effect is best, so the gas flow rate is set to 200sccm O2+100sccm CF4. The RF power frequency is set to 13.56MHz and the output power is set to 600W. When the protective layer thickness is 30um, it can be completely removed after 15min of treatment. Plasma equipment includes but is not limited to plasma jets and plasma chambers, and the processing atmosphere can be atmospheric or vacuum. Depending on the cleaning area, the plasma chamber is more efficient for processing large surfaces; the plasma jet is relatively flexible and is suitable for cleaning workpieces in places where complex structures are difficult to clean, or where parts are too large to fit into the vacuum plasma chamber in the chamber.
[0047] S7. Final surface treatment
[0048] The workpiece after the above treatment is cleaned to completely remove the UV light-cured protective layer and then dried to obtain a finished smooth workpiece without burrs.
[0049] Since the formation of burrs is related to the inherent properties of the workpiece material, it is difficult to fundamentally avoid their formation during the processing process. Therefore, through steps S2 and S3, a UV light-cured protective layer with adjustable hardness and thickness is prepared. The UV light-cured protective layer is used as a medium to cover the workpiece surface under the processing surface. During the micro-nano structure processing, the lateral flow of the boundary material is suppressed, thereby achieving the purpose of suppressing the formation of burrs on the workpiece surface.
[0050] Through the S5 and S6 steps, solvent combined with plasma wet and dry two-step cleaning is highly efficient. First, most of the UV light-cured protective layer is removed by solution immersion, which greatly saves the cost and time of subsequent plasma treatment. Then, oxygen plasma is used to further enhance the cleaning ability, and the cleaning effect is more significant. Compared with the use of acidic and alkaline solutions to clean, which may cause corrosion to the surface, plasma cleaning will not damage the processed structure and has higher surface quality.
[0051] Embodiment 2:
[0052] like Figure 1 As shown, an embodiment of the present invention provides a process method for suppressing the generation of burrs in micro-nano structure processing, comprising the following steps:
[0053] S1. Surface preparation
[0054] First, the surface of the plastic material workpiece is cleaned and dried.
[0055] S2. Spin coating UV adhesive protective layer
[0056] The UV glue is spin-coated onto the surface of the workpiece by a glue spreader to form a UV light-curing protective layer, and the thickness of the UV light-curing protective layer is kept at 2 μm by controlling the spin-coating speed and time; when the workpiece to be processed is a material with poor adhesion to the UV glue, the surface of the workpiece is first subjected to an adhesion enhancement treatment before spin coating, and the adhesion enhancement treatment includes but is not limited to electroplating, thermal spraying and vapor deposition; the UV light-curing protective layer includes but is not limited to UV photoresist used in photolithography and UV glue used for bonding and packaging.
[0057] S3. UV curing and thermal baking
[0058] The spin-coated workpiece is placed in a UV curing machine to cure the UV light-cured protective layer by ultraviolet light for 10 seconds, and then heat-dried with the temperature controlled at 150°C for 5 minutes.
[0059] S4. Machining
[0060] The processed workpiece is subjected to mechanical processing. The processing methods include but are not limited to single-point turning, milling, high-speed fly cutting and ultrasonic vibration-assisted cutting. In order to ensure the applicability of the process, the cutting structure must be a non-adjacent structure containing a plane to ensure that the burr can be transferred to the protective layer. The processing structure includes but is not limited to holes, trapezoidal grooves and serpentine grooves.
[0061] S5. Solution immersion treatment
[0062] The processed workpiece is immersed in a photoresist cleaning agent for 10 minutes. The photoresist cleaning agent used includes but is not limited to inorganic solvents and acidic and alkaline reagents. At the same time, in order to improve the processing efficiency, an ultrasonic cleaning device can be used during the solution immersion process.
[0063] S6. Plasma treatment
[0064] The workpiece after immersion treatment is placed in a vacuum plasma chamber, O2 is used as the reaction gas, CF4 is used as the auxiliary gas, and O2 plasma is excited by a radio frequency power supply in the vacuum chamber through a capacitive coupling method. The main component of the UV light-cured protective layer is carbon-containing organic matter. The high-energy particles in the plasma react with the protective layer to generate CO2 and other gases and are discharged, thereby achieving a cleaning effect and removing the UV light-cured protective layer. This process does not require the introduction of Ar as a medium gas; when O2 and CF4 are introduced at a ratio of 2:1, the plasma cleaning effect is best, so the gas flow rate is set to 200sccm O2+100sccm CF4. The RF power frequency is set to 13.56MHz and the output power is set to 600W. When the protective layer thickness is 30um, it can be completely removed after 15min of treatment. Plasma equipment includes but is not limited to plasma jets and plasma chambers, and the processing atmosphere can be atmospheric or vacuum.
[0065] S7. Final surface treatment
[0066] The workpiece after the above treatment is cleaned to completely remove the UV light-cured protective layer and then dried to obtain a finished smooth workpiece without burrs.
[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A process for suppressing the generation of burrs in micro-nano structure processing, characterized in that: The following steps are involved: S1. Surface preparation First, the surface of the plastic material workpiece is cleaned and dried; S2. Spin coating UV adhesive protective layer The UV glue is spin-coated onto the surface of the workpiece by a glue spreader to form a UV light-curing protective layer, and the thickness of the UV light-curing protective layer is controlled to be 2-30 μm by controlling the spin-coating speed and time; S3. UV curing and thermal baking The spin-coated workpiece is placed in a UV curing machine to cure the UV light-cured protective layer by ultraviolet light for 10-40 seconds, and then heat-dried at a temperature of 150-200°C for 5-10 minutes to regulate the hardness of the photoresist protective layer; S4. Machining The processed workpieces are subjected to mechanical processing, and the processing methods include but are not limited to single-point turning, milling, high-speed fly cutting and ultrasonic vibration-assisted cutting. The processed structure must be a non-adjacent structure including a boss; S5. Solution immersion treatment Soak the processed workpiece in the photoresist cleaning agent for 10 minutes; S6. Plasma treatment Use oxygen plasma equipment to treat the workpiece after solution immersion; S7. Final surface treatment The workpiece after the above treatment is cleaned to completely remove the UV light-cured protective layer and then dried to obtain a finished smooth workpiece without burrs.
2. The process for suppressing the generation of burrs in micro-nanostructure processing according to claim 1, characterized in that: In the step S2, when the workpiece to be processed is a material with poor adhesion to the UV glue, the surface of the workpiece is first subjected to an adhesion enhancement treatment before spin coating, and the adhesion enhancement treatment includes but is not limited to electroplating, thermal spraying and vapor deposition; the UV light-curing protective layer includes but is not limited to UV photoresist used in photolithography processes and UV glue used for bonding and packaging.
3. The process for suppressing the generation of burrs in micro-nanostructure processing according to claim 1, characterized in that: The processed structures in step S4 include but are not limited to holes, trapezoidal grooves and serpentine grooves.
4. The process for suppressing the generation of burrs in micro-nanostructure processing according to claim 1, characterized in that: In the step S5, the photoresist cleaning agent includes but is not limited to an organic solvent, an acidic or alkaline photoresist cleaning agent.
5. The process for suppressing the generation of burrs in micro-nano structure processing according to claim 1, characterized in that: In the step S6, the plasma equipment includes but is not limited to a plasma jet and a plasma chamber, and the processing atmosphere can be atmospheric or vacuum.
6. The process for suppressing the generation of burrs in micro-nanostructure processing according to claim 1, characterized in that: The S6 step is specifically as follows: The workpiece after immersion treatment is placed in a vacuum plasma chamber, O2 plasma is excited, and high-energy particles react with the UV light-cured protective layer through chemical reactions to generate gaseous reactants to remove the protective layer. The RF power frequency is 13.56MHz, the input power is 600W, O2 and CF4 are used as reaction gases, the flow rate is 200sccm O2+100sccm CF4, and the processing time is 15min.
Citation Information
Patent Citations
Manufacturing method of low-cost micronano integrated structure
CN102897709A
Preparation method of solar photovoltaic glass with micro-nano antireflection layer
CN107863393A
Discharging burr removal processing method for plasma tip
CN110394694A
Method for solving problems of burrs and photoresist removing residues in coating process of photoetching technology
CN112864004A
Method for removing micropore burrs of aluminum anodic oxidation small-hole part
CN116103721A